Piles and pile foundations - Viggiani, Carlo; Mandolini, Alessandro; Russo, Gianpiero (Abingdon, Oxon. : Spon Press, 2012)
'Piled foundations are generally designed using empirical methods, in particular the traditional capacity based approach on which the majority of codes of practice are based. However in recent years the analysis of pile groups and piled rafts has undergone substantial development in the light of new research and the mechanisms for the interactions between piles, soil and rafts or caps have been largely clarified. Paradoxically, with relatively large piled rafts it has been found that a design based on the criterion of serviceability, with the limitation of absolute and/or differential settlement, not only allows a more rational and economical design, but is also simpler and more reliable than one based on the traditional approach. This book provides an overview of present design practice of piled foundations, under both vertical and horizontal loads, and then a presentation of recent advances in the analysis and design of piled rafts. Altogether it forms a thorough guide to the design and analysis of efficient and effective piled rafts, and it also serves as a useful design handbook for traditional pile foundations'--
Includes bibliographical references (p. [260]-272) and index.
Keywords: Piling (Civil engineering)